Intervenção em depressão para os usuários da Unidade Básica de Saúde Antônio Monteiro dos Reis, no Município de Brasiléia - Acre - Yonaris Rodriguez Samon (2018)
Depression is a mental disorder that causes disability, contributes in a very important way to the global burden of disease. It is estimated that 350 million people of all ages suffer from this depressive disorder. This study aims to carry out an intervention to increase the care of users with depression in the area covered by the Antônio Monteiro dos Reis Basic Health Unit, in the city of Brasiléia, Acre. In order to carry out the health intervention project in our area of coverage, a situational diagnosis was necessary to identify health problems. The high incidence of vectors (Aedes aegyptis) and a high number of diseases transmitted by them, such as Dengue, Zika and Chikungunya, have been identified. High incidence of chronic noncommunicable diseases such as hypertension, diabetes mellitus, obesity, cancer, consumption elevated cholesterol, increased triglycerides and obesity, an increase in people with depression, an increase in syphilis, especially in pregnant women, and the low attendance of children older than one year to consultations and vaccines. Then prioritized according importance, urgency, coping ability and punctuation, increased depression. A description and explanation of this problem was made and the causes identified. For the construction of the action plan a bibliographical research was carried out on the proposed problem to raise the existing evidence related to the theme. We built the action plan to be implemented, discussed, evaluated and monitored by the UBS Antônio Monteiro dos Reis family health team, in order to extend care to users suffering from depression and thus improve people's emotional health by reducing their potential their personal lives, within the family and in society.